Epignathus with Cervical Lymphangioma - Rohit Lal; Vinit Kumar Thakur (Wolters Kluwer Medknow Publications, 2024)
The occurrence of teratoma is 1 in 4,000 live births. Head-and-neck region teratoma (epignathus) is rare. These patients present with facial disfigurement, respiratory problems, and difficulty in feeding. It warrants early excision to avoid any morbidity or mortality due to airway obstruction. We describe the management of a patient with pedunculated epignathus with cervical lymphangioma.